ENHANCEMENT OF THE JUVENILE CRIME PREVENTION SYSTEM IN THE REPUBLIC OF KAZAKHSTAN: CHALLENGES, TRENDS, AND STRATEGIES FOR MODERNIZATION - Kuanysheva, Indira (E-Journal VFU, 2025)
Juvenile delinquency in Kazakhstan remains a serious problem, with an increase recorded in 2025. The main causes include weak inter-agency coordination, the absence of a unified law on juvenile justice, duplication of functions, and neglect of social risk factors. Preventive measures remain focused on the consequences rather than on the adolescents themselves, highlighting the importance of actively using digital technologies for monitoring and coordinating the work of relevant authorities.